(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND: Due to persistent organ shortage, the selection criteria for living kidney donors have broadened to include elderly donors and those with co-morbidities. As little is known about metabolic health after living kidney donation, this prospective, multicentre cohort study explored metabolic changes among living kidney donors, with a particular focus on weight trajectories. METHODS: We analysed metabolic and cardiovascular parameters before and after living kidney donation in 466 consecutive living kidney donors recorded in the Swiss Organ Living-Donor Health Registry between January 2018 and August 2022. Outcomes included weight, blood pressure, haemoglobin A1c (HbA1c) levels, and the occurrence of new-onset type 2 diabetes mellitus, arterial hypertension and cardiovascular diseases. Donors were stratified by predonation body mass index (BMI) and by postdonation weight change. RESULTS: Obese donors (BMI ≥30 kg/m²) more frequently had pre-existing hypertension at baseline than non-obese donors (31.6% vs 18.3%, p = 0.03). During follow-up (median 2.9 years), 6% of living kidney donors developed arterial hypertension, 2.6% developed cardiovascular diseases and 1.1% developed type 2 diabetes mellitus. Obese donors had a higher incidence of postdonation type 2 diabetes mellitus than non-obese donors (p = 0.01). Changes in BMI postdonation were not correlated with age or predonation BMI. Donors with postdonation weight gain had slightly higher follow-up blood pressure, but no clear differences in rates of new-onset hypertension or type 2 diabetes mellitus were observed between weight-change groups. CONCLUSIONS: This exploratory analysis suggests that living kidney donation is generally metabolically safe. While metabolic changes were modest overall, obesity at the time of donation was associated with a slightly higher frequency of postdonation type 2 diabetes mellitus, underscoring the importance of counselling on lifestyle modification before donation.